The Importance of Teacher’s Motivation in Improving the Quality of Students’ Education - Suhendar Suhendar (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Fundamentally, teacher’s motivation in the framework of improving the quality of students’ education is considerably required and shall constitute a value-based effort for the teacher, as he/she is actively involved in pedagogical process of learning. In addition, teacher has an ultimate role in the process of building students ‘education. In view of that, the students’ ideal characters building can be accordingly attained if it is performed by a highly qualified teacher. For that reason, teacher supposedly recognizes systematically the matters which can satisfy the fulfillment of student’s education quality and the characteristic of education itself in the society. Academically, the writer specifically analyzes the problem as follows: 1) How important is the teacher’s motivation in improving students’ education quality? 2) Why is teacher’s motivation very crucial in the society?; and 3) what are the steps of teacher’s motivation fulfillment in improving students’ education quality ?. To sum up teacher’s motivation in improving student’s education quality is very important and to such an extent it is very crucial as teacher is the actor of agent of change in the society. For that reasons, teacher should use his/her best endeavor to realize such purpose through a value-based motivation developments.